Endothelial dysfunction and increased platelet reactivity in patients with acute coronary syndrome and undiagnosed COPD: insights into the SCAP trial. Issue 4 (5th October 2017) - Pavasini, Rita; Vieceli dalla Sega, Francesco; Gallo, Francesco; Passarini, Giulia; Papi, Alberto; Contoli, Marco; Campo, Gianluca
Unknown/undiagnosed chronic obstructive pulmonary disease (UCOPD) frequently coexists and negatively impacts in the short- and long-term prognosis of patients with coronary artery disease (CAD) treated with percutaneous coronary intervention (PCI) [1]. In the Screening for COPD in Acute coronary syndromes Patients (SCAP) trial [2], we recently showed that COPD is frequently undiagnosed in ccute coronary syndrome (ACS) patients with smoking history. Furthermore, we found that a simple screening procedure including peak expiratory flow measurement and respiratory health status questionnaire (RHSQ) might be administered before hospital discharge to discriminate those at risk of UCOPD. In the SCAP study, it was pre-specified that an ancillary analysis aimed to clarify if UCOPD was related to abnormalities in platelet reactivity and endothelial function. Endothelial dysfunction and increased platelet reactivity in acute coronary syndrome with unknown/undiagnosed COPD http://ow.ly/SVEg30eExbK